Marketing Strategy Of Peanuts (Arachis Hypogaea L.) In Among Tani V Farmer Group, Rejuno Village, Karangjati District, Ngawi - Jalil, Abdul; Suswadi; Prasetyo, Agung (Journal of Rural and Urban Community Studies, 2025)
This study aims to (1) identify internal factors that act as strengths and weaknesses in peanut marketing by the Among Tani V Farmer Group in Rejuno Village, Karangjati District, Ngawi, (2) identify external factors that serve as opportunities and threats in marketing, and (3) formulate appropriate marketing strategies to enhance the competitiveness of peanuts in the region. This research employs a descriptive qualitative method with purposive sampling. Data collection was conducted through observation, in- depth interviews, and document studies using primary and secondary data. Data analysis involved the IFE and EFE matrices to assess internal and external factors, an IE matrix to determine marketing strategies, and SWOT analysis to formulate the most suitable strategy. The results showed that the IFE matrix score was 2.1, and the EFE matrix score was 2.84, indicating the need for strategic marketing improvements.